2023
DOI: 10.3390/ijerph20043300
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D—A Risk Factor for Bone Fractures in Children: A Population-Based Prospective Case–Control Randomized Cross-Sectional Study

Abstract: Background: Vitamin D is an essential component in calcium metabolism. Seasonality, advanced age, sex, dark skin pigmentation, and limited exposure to sunlight were reported as causes of vitamin D deficiency. This study aims to determine whether children with lower levels of vitamin D suffer more fractures than those with sufficient levels. Materials and Methods: Our institution underwent a prospective case–control randomized cross-sectional single-blinded study that included 688 children. They were split into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…Vitamin D is a pleiotropic hormone that plays a role in calcium–phosphorus metabolism as well as in the bone health [ 14 , 30 ]. Its proper supplementation in OI helps to prevent the secondary increase in PTH and the following increase in bone turnover [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is a pleiotropic hormone that plays a role in calcium–phosphorus metabolism as well as in the bone health [ 14 , 30 ]. Its proper supplementation in OI helps to prevent the secondary increase in PTH and the following increase in bone turnover [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, early randomized controlled trials provided indirect evidence that calcium intake increases bone mineral density and reduces fracture risk, and a recent trial showed modest reduction in fracture incidence with vitamin D and calcium supplementation 171-175 . Malnutrition has shown to increase susceptibility to infections, prolong hospital LOS, and increase medical costs, whereas oral nutrient supplementation has shown to reduce hospital LOS and costs 12 .…”
Section: The Impact Of Malnutrition In Orthopaedic Surgerymentioning
confidence: 99%
“…The pediatric Subjective Global Nutrition Assessment has shown good correlation with serum albumin levels in predicting 30-day postoperative complications and prolonged hospital LOS after major surgery 169,170 . However, early randomized controlled trials provided indirect evidence that calcium intake increases bone mineral density and reduces fracture risk, and a recent trial showed modest reduction in fracture incidence with vitamin D and calcium supplementation [171][172][173][174][175] . Malnutrition has shown to increase susceptibility to infections, prolong hospital LOS, and increase medical costs, whereas oral nutrient supplementation has shown to reduce hospital LOS and costs 12 .…”
Section: Pediatricsmentioning
confidence: 99%
“…The rate of nonunion is reported as 6–33% [18] and is associated with inadequate reduction [50] and prolonged immobilization. This may also be improved with Vitamin D supplementation in deficient patients [14,21 ▪ ]. Premature growth arrest occurs in 5–65% of cases [23] and results from direct trauma to the physis or vascular injury at the time of fracture but may also be a consequence of surgical intervention, particularly if surgical implants cross the growth plate.…”
Section: Complicationsmentioning
confidence: 99%
“…They are also usually caused by high energy trauma and are less commonly due to pathological bone lesions [20], birth trauma and seizures. Nonaccidental injury should be considered in nonambulatory patients [21 ▪ ]…”
Section: Introductionmentioning
confidence: 99%